Islamic Boarding Schools in Lombok Pendidikan Islam Sebagai Penangkal Krisis Identitas Pemuda-Pemudi Muslim - Muji Agus Sofiyandi (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The phenomenon of identity crisis among young Muslim men and women is increasingly worrying with the rapid flow of globalization and modernization. This study aims to analyze the role of Islamic education in fortifying the younger generation of Muslims against this identity crisis using a qualitative literature study approach. The results show that holistic Islamic education integrating cognitive, affective, and conative aspects can strengthen Islamic identity, build moral resilience, and foster a critical attitude towards external cultural influences. Islamic education also plays a role in the internalization of values and character formation. This study recommends strengthening the curriculum, contextual learning methods, and collaboration between families, schools, and communities in addressing the identity crisis of young Muslims.